Transcranial electrical stimulation modifies the neuronal response to psychosocial stress exposure - Antal, Andrea (Hum Brain Mapp, 2013)
Stress is a constant characteristic of everyday life in our society, playing a role in triggering several chronic disorders. Therefore, there is an ongoing need to develop new methods in order to manage stress reactions. The regulatory function of right medial‐prefrontal cortex (mPFC) is frequently reported by imaging studies during psychosocial stress situations. Here, we examined the effects of inhibitory and excitatory preconditioning stimulation via cathodal and anodal transcranial direct current stimulation (tDCS) on psychosocial stress related behavioral indicators and physiological factors, including the cortisol level in the saliva and changes in brain perfusion. Twenty minutes real or sham tDCS was applied over the right mPFC of healthy subjects before the performance of the Trier Social Stress Test (TSST). Regional cerebral blood flow (rCBF) was measured during stimulation and after TSST, using pseudo‐continuous arterial spin labeling (pCASL). Comparing the effect of the different stimulation conditions, during anodal stimulation we found higher rCBF in the right mPFC, compared to the sham and in the right amygdala, superior PFC compared to the cathodal condition. Salivary cortisol levels showed a decrease in the anodal and increase in cathodal groups after completion of the TSST. The behavioral stress indicators indicated the increase of stress level, however, did not show any significant differences among groups. In this study we provide the first insights into the neuronal mechanisms mediating psychosocial stress responses by prefrontal tDCS. Hum Brain Mapp 35:3750–3759, 2014. © 2013 Wiley Periodicals, Inc.